Perempuan sebagai Pewaris: Transformasi Hukum Kewarisan dalam Bilangan 27:7 sebagai Manifestasi Keadilan Ilahi di Tengah Dominasi Patriarkat - Rudolf John Ritiauw (JUITAK: Jurnal Ilmiah Teologi dan Pendidikan Kristen, 2025)
Ancient Israelite tradition reflects a patriarchal social structure that positioned men at the center of social, legal, and religious authority, resulting in limitations on women’s rights and roles, including access to inheritance law. This article addresses theological and juridical issues concerning the mechanism of legal change through the narrative of the daughters of Zelophehad in Numbers 27:1-11, which constitutes a significant turning point in Israelite legal tradition. The research problem focuses on the lack of attention in previous studies to the theological meaning of God’s decision in Numbers 27:7, as earlier research has tended to emphasize socio-cultural aspects, contextual relevance, or purely linguistic analysis. This study employs a qualitative approach based on a literature review, utilizing Hebrew textual exegesis, analysis of Israel’s patriarchal context, and a critical reading through the lens of feminist theology. The findings indicate that the daughters of Zelophehad’s claim was not merely a response to a legal vacuum, but a conscious action that positioned women as active subjects in the process of legal formation. God’s decision affirming their claim underscores divine justice that transcends the limitations of the patriarchal system and corrects institutionalized structural injustice. The conclusion affirms that this narrative presents God as the source of justice who sides with the restoration of the dignity of marginalized groups and opens space for women’s participation as agents of legal change. The novelty of this study lies in its theological interpretation that positions women not only as recipients of inheritance rights, but as pioneers of legitimate and divinely recognized legal transformation. These findings contribute to the development of feminist theology and Old Testament legal studies, while also providing a reflective foundation for gender equality discourse in contemporary theological and religious practice across cultures.